Using corporate cloud for teaching Cisco Network Academy courses: a case study - Nadiia R. Balyk; Yaroslav Ph. Vasylenko; Vasyl P. Oleksiuk; Olesia R. Oleksiuk; Galina P. Shmyger (Academy of Cognitive and Natural Sciences, 2024)
This paper explores using the university's corporate cloud to teach some Cisco Network Academy courses, a common feature of many universities. The paper presents two cloud labs based on the open-source platforms Apache CloudStack and EVE-NG Community Edition and operating on the IaaS model. The labs support the courses "CCNA CyberOperations" and "DevNet Associate Fundamentals Courses," allowing students to access various virtual machines, store their state, analyse traffic, and visualise network topologies. The paper also reports on the students' satisfaction with the courses based on a survey of students majoring in "Secondary Education. Computer Science". The survey results were statistically analysed using the Rasch model with MiniSteps software and R language. The students gave positive feedback on the online curriculum materials, the virtual machines, the clarity and simplicity of the lessons, and the multiple ways of presenting information.